A brief overview of genetic algorithms - Szabó, Kristóf (Design of Machines and Structures, 2023)
This article examines the topic of Genetic Algorithms, discussing the basic concepts and terminology related to Genetic Algorithms. The advantages, disadvantages and limitations of the mentioned algorithms are defined. The different population models and the process of parent selection are presented, as well as the areas of application of the procedure are summarized.